PHILOSOPHICAL WORLDVIEW OF THE FIRST GENERATION OF KYRGYZ NATIONAL INTELLIGENTSIA (20S-30S OF CENTURY XX) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article is devoted to the influence of the scientific and methodological activities of the first generation of enlightened people of Kyrgyzstan (Intelligentcia) in the 20-30s of the twentieth as advanced part of the population of the 20s-30s of XX Century. They have changed the philosophical worldview of the people. Perceiving with delight the new, hitherto unknown teaching of Marxism, proclaiming good slogans about equality, brotherhood and a light future, the most advanced people of their years, at the same time opposed the real actions of the leaders of the new society, manifested by the October Revolution. The philosophical outlook of the young Kyrgyz intelligentsia, formed under the influence of Marxist dialectical materialism, at the same time was subjected to painful analysis and rejection of many theses of the Stalinist type of Marxism-Leninism.
Keywords: The Kyrgyz intelligentcia, marksist philosophy, red terror, Kyrgyz alphabet, Stalinism, repressions, lessons by Tynystanov.